Percepção de moradores de um aglomerado em Belo Horizonte, sobre os fatores relacionados à mobilidade urbana - Luiza de Marilac Resende (2016)
Throughout history, the mobility phenomenon as a process has ensured vital conditions to individuals, coming to represent the only resource for primitive men to obtain food and for the survival of their group. Men´s mobility was accentuated by the Industrial Revolution and a tendency of the rural population shifts to urban areas. According to the World Health Organization, in 2007, more than 50% of the world´s population already lived in urban areas. In Brazil in 2010, the urbanization rate in the country reached 84.0%. Given this fact, mobility has become a challenge and the subject has been approached increasingly, being handled by the term "urban mobility". Although since 2012 there is an urban mobility policy in Brazil, the main focus has been placed on motorized transport, but the walk on foot has been less considered, or the concern concentrated in physically challenged people and the elderly. Belo Horizonte adopted the Family Health Program (PSF) as a strategy for the organization of health services, which provides in addition to attendance at the Health Unit, the active search of cases, carried out by multidisciplinary teams through home visits. In one of these visits, one of the researchers of this study found mobility barriers of an elderly patient. Living in a steep location, to leave the house, the patient had to go down hills and stairs to reach the street, extremely busy, with high vehicles circulation, narrow sidewalks and with various barriers. This study aimed to understand how the difficulties and facilities of urban mobility are perceived among the residents of the shanty town, in Belo Horizonte. We opted for the qualitative methodology, using the recorded home interview, transcribed and subjected to content analysis. Initially, it was determined the study area, being located 10 points in the neighborhood, considered critical to mobility, selected by convenience Georeferencing was done for the area. The data were spatially in Google Earth.The main factors related to urban mobility, mentioned by the residents were selected and grouped into the following themes: topography (hills and stairs), roads (traffic and flooding by rainwater), sidewalks (uneven, narrow and busy), safety traffic (being run over, especially by motorcycles, lack of signage, more traffic than behaved on the streets), social capital and belonging (some resilience, improvement wishes, solidarity, bond, respect, social capital). There are precarious conditions for mobility, especially for pedestrians, but it was observed the possibility of changes starting from the community.